Numerical simulation of depressurization exploitation in class 1 hydrate reservoirs under different development factors in Shenhu area, South China sea - Wei, Na; Li, Cong; Zhao, Xingxin; Li, Haitao; Zhang, Liehui; Zhao, Jinzhou; Kvamme, Bjørn; Coffin, Richard B. (Frontiers in Earth Science, 2024)
Most of the implemented marine gas hydrate test exploitation in the world adopt the depressurization method to break down the hydrate in the reservoir into natural gas and then extract it, but because the gas production results are still a certain distance away from the commercial exploitation, and it mainly stays in the stage of theoretical research and trial exploitation. Based on two trial productions in the Shenhu area of the South China Sea, this study established a model for hydrate exploitation and investigated the impact of different well types on the recovery rates of hydrates and free gas in different development layers during depressurization. For the Class 1 hydrate reservoirs, horizontal wells are the optimal solution to extract hydrate and free gas simultaneously when exploiting the hydrate three-phase layer. Meanwhile, the effect of different well spacing in vertical wells on the recovery rate of hydrate and free gas was studied. It is found that the best recovery efficiency is achieved when the spacing between two wells is 80m. The lower the bottom flow pressure of the well, the higher the production capacity, but its influence is limited.